PROSEDUR PEMERIKSAAN COLON IN LOOP PEDIATRIK DI INSTALASI RADIOLOGI RSU PKU MUHAMMADIYAH BANTUL (Studi Kasus Pada Pasien Dengan Klinis Konstipasi Kronis Berusia 3 Tahun) - Reksal Makaramah; Sofie Nornalita Dewi; Ayu Mahanani (Journal of Innovation Research and Knowledge, 2025)
Background: The Colon in Loop examination is an important radiographic procedure for evaluating cases of chronic constipation in pediatric patients. At PKU Muhammadiyah Bantul Hospital, there are differences in procedures compared to existing literature, particularly regarding patient preparation, types of contrast media used, and projection techniques. The aim of this study is to determine the procedure for the Colon In Loop examination, patient preparation, types of contrast media used, and projection techniques at the Radiology Installation of PKU Muhammadiyah Bantul Hospital.Method: This research employed a qualitative approach with a descriptive method and case study design. The study was conducted at the Radiology Installation of PKU Muhammadiyah Bantul Hospital from May to June 2025, involving three radiographers and one radiology specialist as subjects. Data collection methods included observation, interviews, documentation, and literature review. Data analysis was performed through data collection, data reduction, data presentation, and conclusion drawing.Result: The results indicated that the Colon In Loop examination procedure only required general preparation and did not involve any special preparation. The contrast media used was water-soluble, and the antero-posterior (AP) projection was employed, as it was adjusted to the non-cooperative condition of pediatric patients. Conclusion: The procedure for the Colon In Loop examination in pediatric patients at the Radiology Installation of PKU Muhammadiyah Bantul Hospital involved only general preparation without any special preparation. The contrast media used was a water-soluble mixture of iohexol and NaCl, administered gradually, as its non-ionic nature prevents excessive absorption by the body and provides stability when entering the bloodstream, making it safer for patients. The use of the antero- posterior (AP) projection was tailored to the non-cooperative condition of pediatric patients. It is recommended that examinations be conducted using X-ray equipment equipped with fluoroscopy to visualize the flow of contrast media